Reformulating The Concept of State Principles Based on Ideological and Technocratic Strategic as A Sustainable Development Direction - Bagus Oktafian Abrianto; Farid Ibrahim; Xavier Nugraha (LAW REFORM, 2020)
National development planning model with its long-term time dimension in Indonesia is carried out with the National Long-Term Development Plan (RPJPN) which replaces the Planned Overall National Development (PNSB) and the General Outlines of the Principles of the State (GBHN). Based on the analysis of the data obtained, it can be seen that since 2004 the use of the RPJN has turned out to cause fluctuating dynamics in the existing development outcomes. The occurred changes resulted in inconsistencies in the direction of development when there was a change of state development actors such as President, Governor, Regent/ Mayor, and other state institutions. The reason for this is that there is no permanent structure that can be used as a reference for a long-term development program that will be carried out by the managing state institutions, particularly the government. Based on this, the aim of this study was to create a form of reformulation of the principles of the state. This research was a normative research with a statutory, historical and conceptual approaches. To answer this problem, the idea of the state principles was born which departed from combining the advantages of PNSB, GBHN, and RPJPN which were then packaged into a new state principle system, with ideological principle and technocratic strategy.